The distribution, biota and stratigraphy of a Windsor Group limestone (Mississippian) and associated sediments in the Quaco Head area of New Brunswick - Plint, A.; Ryan, R.; van de Poll, H. (Atlantic Geology, 1983)
Re-mapping of the Quaco Head area of southern New Brunswick has shown that Windsor Group Limestones have a more extensive distribution than was previously recognized. The limestone at Quaco Head is up to 8.5 m thick and rests unconformably on basalts Precambrian (Coldbrook) age. The limestone, which now consists mainly of microsparite, shows prominent algal lamination including laterally-linked hemispheroids and large, isolated 'heads', up to 80 cm high. Stratified and laminated limestone with a pseudo-oolitic texture occupies the troughs between the 'heads'. The limestone is capped by 2 m of calcibreccia, overlain by red, matrix supported polymict conglomerates, laminated sandy siltstones and coarse, clast-supported polymict conglomerates. The limestone lithofacies. form a regressive sequence, deposited in shallow subtidal and intertidal environments, close to the shore of the Windsor sea. The overlying clastic sediments probably record the onset of vigorous alllclastlc alluvial fan sedimentation in response to local fault movement in ?Late Visean (Hopewell Croup) times.